RECREATIONAL FACTORS AS A CATEGORY OF RECREATIONAL PROCESS - Vykhliaiev, Yu. M.; Dudorova, L. Yu.; Petsenko, N. I. (Rehabilitation and Recreation, 2024)
The purpose of the paper is to analyse the fixed assets of recreational process, role and place in this process of such constituent as recreational factors. Research methods: analysis and generalization of the data of scientific and methodical literature regarding the means of the recreational process, scientific and methodical substantiation of recreational means, their application and essence, theoretical elaboration of the authors’ own practical experience in teaching the disciplines “Recreational technologies” and “Theory and technologies of health-recreational motor activity”. Results. The tasks of recreation are: restoration and strengthening of physical condition, health; prevention and prevention of possible injuries or diseases; elimination of residual phenomena accompanying a person after injuries or illnesses; The recreational process is used in the post-hospital stages of recovery with the predominant use of physical exercises, but their health-improving orientation is questioned by the authors, if they are not supported by recreational factors, by which the authors understand the performance conditions that contribute to both the strengthening of the restorative processes and the improvement of the functional state of the majority human systems and organs. There are many exercises, the performance of which is accompanied by negative factors, such as air gassed with street dust, a hard surface that causes unwanted shocks for the spine, joints, feet, non-compliance with the methodological and practical principles of the theory of physical education, for example, episodic classes, etc. Recreational factors – on the contrary, strengthen the health component of exercise, for example, a water environment from mineral springs or a soft grass path in a pine forest, shoes with elastic insoles, high-quality air with phytoncides and an increased oxygen content, and if this path is located on the seashore, with ions of iodine, sodium and calcium of the sea breeze, the recreational component can reach higher ratings. Conclusions. Identification of recreation as a process of improving the health of the population through the use of physical exercises enhanced by recreational factors with the task of restoring and improving physical condition and health; prevention and prevention of possible injuries or diseases; elimination of residual phenomena that accompany a person after injuries or illnesses, allows to more clearly understand the paradigm of its application and its place in the theory and methodology of physical education.